Foot reflexology on nausea and vomiting: A systematic review - Soheila Shamsikhani; Mahsa Hosseini (Journal of Integrative Nursing)
Nausea and vomiting are physiological responses that react to various bodily conditions and play a protective function. Medicinal and nonmedicinal methods, including complementary medicine, treat nausea and vomiting. The current research aims to investigate the effectiveness of foot reflexology as a complementary medicine method for nausea and vomiting. Based on PRISMA 2020, PubMed, Web of Science, and Scopus were searched until October 2, 2024, using a search strategy approved by two researchers. Only randomized controlled trial studies were included in this research. No limitations or filters were applied. The inclusion criteria were selected based on the PICOS framework, and the studies were evaluated according to the National Institutes of Health quality assessment tool, which is related to controlled intervention, and were evaluated by two researchers. Finally, six studies were included in this review. Eighty-four percent of studies were conducted in Asia. Three records are from Iran, and two are from Turkey, and one is from France. The results showed that nausea and vomiting improved in all studies. In most studies (67%), four sessions or less led to improved outcomes. Rhodes index of nausea, vomiting, and retching and visual analog scale were utilized to assess nausea and vomiting. The current systematic review indicated that foot reflexology as a noninvasive intervention could improve nausea and vomiting in patients with cancer problems, pregnancy, hemodialysis, and laparoscopic cholecystectomy.